2018
DOI: 10.1002/eat.22975
|View full text |Cite
|
Sign up to set email alerts
|

The role of self‐esteem in the treatment of patients with anorexia nervosa – A systematic review and meta‐analysis

Abstract: Objective: We aimed to provide a comprehensive overview of the role of self-esteem in the treatment of patients with anorexia nervosa (AN). Specifically, our objectives were to investigate the differences in self-esteem between individuals with AN and healthy controls, or individuals with other eating disorders, and to examine self-esteem as an outcome, predictor, moderator, and mediator in AN treatment.Method: The databases PsycINFO, PSYNDEXplus, Ovid MEDLINE ® , and ProQuest were searched for studies publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 104 publications
4
18
0
1
Order By: Relevance
“…This treatment resulted in significantly lower discharge scores on ED symptoms and outcomes relevant to anxiety (including experiential avoidance [Kashdan, Barrios, Forsyth, & Steger, ] and anxiety sensitivity [McNally, ]), relative to admission (Thompson‐Brenner, Boswell, Espel‐Huynh, Brooks, & Lowe, ). As another example, transdiagnostic interventions that target low self‐esteem, such as through increasing confidence and interpersonal effectiveness (e.g., interpersonal psychotherapy [e.g., Rieger et al, ], dialectical behavior skills [Linehan, ]), could be efficacious (e.g., Kästner, Löwe, & Gumz, ; Vall & Wade, ).…”
Section: Discussionmentioning
confidence: 99%
“…This treatment resulted in significantly lower discharge scores on ED symptoms and outcomes relevant to anxiety (including experiential avoidance [Kashdan, Barrios, Forsyth, & Steger, ] and anxiety sensitivity [McNally, ]), relative to admission (Thompson‐Brenner, Boswell, Espel‐Huynh, Brooks, & Lowe, ). As another example, transdiagnostic interventions that target low self‐esteem, such as through increasing confidence and interpersonal effectiveness (e.g., interpersonal psychotherapy [e.g., Rieger et al, ], dialectical behavior skills [Linehan, ]), could be efficacious (e.g., Kästner, Löwe, & Gumz, ; Vall & Wade, ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they would feel a sense of superiority over others based on their eating practices which are the primary focus of their lives. A recent meta-analysis concluded that selfesteem difficulties are highly relevant in the treatment of anorexia nervosa (AN) and that transdiagnostic approaches regarding other eating disorders (such as ON) can be recommended [20]. Despite its relevance in disordered eating and other destructive health behaviors [21], self-esteem was generally found to be unrelated to ON [7,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…It is further noteworthy, that women with AN reported significantly lower IS compared with women without AN. This could reflect low overall self‐confidence of women with AN (Kastner, Lowe, & Gumz, 2019), leading to mistrust in their performance on the HBTT. Future research should investigate, how low IS in AN relates to other aspect of eating disorders pathology (e.g., the difficulty of discriminating bodily signals relating to hunger and satiety).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent study by Körner et al (2019) found power posing to increase state self‐esteem. It would be important to assess whether this effect also occurs in AN populations, who display low levels of self‐esteem (Kastner et al, 2019).…”
Section: Discussionmentioning
confidence: 99%